2017
DOI: 10.1007/s12265-017-9732-6
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Tissue Oxygenation in Metabolic Syndrome Requires Increased Microvascular Perfusion Heterogeneity

Abstract: Metabolic syndrome (MS) in obese Zucker rats (OZR) is associated with impaired skeletal muscle performance and blunted hyperemia. Studies suggest that reduced O2 diffusion capacity is required to explain compromised muscle performance and that heterogeneous microvascular perfusion distribution is critical. We modeled tissue oxygenation during muscle contraction in control and OZR skeletal muscle using physiologically realistic relationships. Using a network model of Krogh cylinders with increasing perfusion as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Distribution of blood flow is more spatially heterogeneous in the obese Zucker rat model of type 2 diabetes, and this perfusion heterogeneity is associated with impaired oxygen uptake. 14,15,24,25 Simulation studies reveal that heterogeneous perfusion results in impaired muscle oxygenation on average, because over-perfused vessels cannot fully compensate for under-perfused vessels. 15,2628 By definition, heterogeneous perfusion not resulting from heterogeneous tissue demand would result in flow/VO 2 mismatch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distribution of blood flow is more spatially heterogeneous in the obese Zucker rat model of type 2 diabetes, and this perfusion heterogeneity is associated with impaired oxygen uptake. 14,15,24,25 Simulation studies reveal that heterogeneous perfusion results in impaired muscle oxygenation on average, because over-perfused vessels cannot fully compensate for under-perfused vessels. 15,2628 By definition, heterogeneous perfusion not resulting from heterogeneous tissue demand would result in flow/VO 2 mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,24,25 Simulation studies reveal that heterogeneous perfusion results in impaired muscle oxygenation on average, because over-perfused vessels cannot fully compensate for under-perfused vessels. 15,2628 By definition, heterogeneous perfusion not resulting from heterogeneous tissue demand would result in flow/VO 2 mismatch. Moreover, these effects would influence skeletal muscle deoxygenation/oxygenation even in cases of normal bulk blood flow and local recruitment of microvascular blood volume/hematocrit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Postulated mechanisms for these dysfunctions include: (1) the capillary rarefaction and increased perfusion heterogeneity in hypertensives impair flow and oxygen delivery to the working muscles; thus, a greater increase in BP is required to achieve perfusion, and (2) the structural alterations in the resistance vasculature may act as a vascular amplifier that further enhances the effects of a hypertensive stimulus, such as exercise. 12,50 In addition, the impaired oxidative capacity suggestive of mitochondrial dysfunction/uncoupling in the skeletal muscle of hypertensive patients could lead to an increase in reactive oxygen species, reducing endothelial NO synthase, and resulting in a decrease NO bioavailability. 46 The increased oxidative stress and inflammation further reduces NO, promoting endothelial dysfunction within the small vessels' wall and impairing vasodilation in exercising muscles.…”
Section: Muscle Oxygenation and Bp Responses During Exercisementioning
confidence: 99%
“…21 In support, animal studies have shown that the reduced microvascular distensibility and rarefaction resulted not only in increased skeletal muscle vascular resistance at resting conditions, but also contributed to a blunted functional hyperemia of skeletal muscles at higher levels of metabolic demand, such as, during exercise. 50 Postulated mechanisms for these dysfunctions include: (1) the capillary rarefaction and increased perfusion heterogeneity in hypertensives impair flow and oxygen delivery to the working muscles; thus, a greater increase in BP is required to achieve perfusion, and (2) the structural alterations in the resistance vasculature may act as a vascular amplifier that further enhances the effects of a hypertensive stimulus, such as exercise. 12,50 In addition, the impaired oxidative capacity suggestive of mitochondrial dysfunction/uncoupling in the skeletal muscle of hypertensive patients could lead to an increase in reactive oxygen species, reducing endothelial NO synthase, and resulting in a decrease NO bioavailability.…”
mentioning
confidence: 99%